Leadership, competitive intelligence and Robert Oppenheimer’s pivotal role in the dawn of the nuclear age - Rodica-Cristina BĂLAN-LISEANU (Bulletin of "Carol I" National Defense University, 2023)
In an era of globalization, innovation, and competitive intelligence, the nuclear supply chain is continually evolving and increasing its capabilities. The top-secret operation ALSOS plays a key role in the (re)evolution of atomic energy as the energy of the future, with a constant focus on the responsible use of atomic energy. The US, a nuclear hegemon, has harnessed its leaders to their full potential, with J. Robert Oppenheimer being one of the leading names in charismatic, competitive, and transformational leadership. Through qualitative and content analysis, this article proposes a reflection on the origins and evolution of change in the nuclear field, in a continuous struggle for supremacy, connecting with current desiderata in the sphere of innovation, built on different leadership styles. The interest in leadership is recurrent, and the model of Operation ALSOS, in line with the iconic figure of J. Robert Oppenheimer, is representative of motivating the harnessing of new promises to inspire and revolutionize the world.